Testing The Effectiveness Of Cinnamon (Cinnamomum Burmannii Blume) Ethanol Extract Against Staphylococcus Epidermidis Bacteria - Thania Lewinssky; Anggi Aprilyani (International Journal of Health and Pharmaceutical (IJHP), 2025)
Skin infections caused by Staphylococcus epidermidis are a growing global health concern, exacerbated by increasing antibiotic resistance. This study aimed to evaluate the antibacterial activity of cinnamon (Cinnamomum burmannii Blume) ethanol extract as a natural alternative. A true experimental design with a post-test only control group was used. The population consisted of Staphylococcus epidermidis bacteria, and a total of 25 samples were assigned to five groups, including three extract concentrations (25%, 50%, and 75%), a clindamycin positive control, and a DMSO negative control. Antibacterial activity was tested using the disk diffusion method, and data were analyzed with Kruskal-Wallis and Mann-Whitney tests. The results showed that cinnamon extract effectively inhibited bacterial growth, with the 75% concentration producing the largest average inhibition zone (13.76 mm). While the extract's efficacy was lower than that of clindamycin (16.66 mm), its potential as a natural antibacterial agent is significant. The findings suggest that cinnamon extract can be developed into a topical treatment for skin infections.